2007
DOI: 10.1029/2007je002923
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer hypervelocity dust impacts in low Earth orbit

Abstract: [1] A study has been made of 60 nm thick aluminum films which have been exposed to the space environment outside of International Space Station (ISS) between 2002 and 2004. Field emission scanning electron microscopy has been used to provide high-resolution images of impact features less than 100 nm in diameter and of detailed impact morphologies at different spatial scales. Analysis of images reveals the incident directions and diameters of the impacting particles and allows separation of impacts at hypervelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The estimated flux (Carpenter et al 2007) of the nano dust is consistent with the interplanetary dust distribution.…”
Section: Comparison To Measurements Near 1 Au (Stereo and Iss)supporting
confidence: 62%
See 2 more Smart Citations
“…The estimated flux (Carpenter et al 2007) of the nano dust is consistent with the interplanetary dust distribution.…”
Section: Comparison To Measurements Near 1 Au (Stereo and Iss)supporting
confidence: 62%
“…Possible observations of the nano dust near 1 AU were reported from the International Space Station (ISS: cratering in the exposure foil; Carpenter et al 2007) and from STEREO A and B spacecraft (voltage pulses;Meyer-Vernet et al 2009a).…”
Section: Comparison To Measurements Near 1 Au (Stereo and Iss)mentioning
confidence: 99%
See 1 more Smart Citation
“…If this is the case, the mass input into the ionosphere below 400 km altitude is ∼ 2 · 10 −6 kg s −1 or 55 kg / year, which is ∼ 10 −6 or less of the meteoroid mass input. Nano dust impacts are also suspected to generate impact craters detected on a foil that was exposed to space within the Earth magnetosphere on the International Space Station ISS (Carpenter et al 2005) (also shown in Fig. 2).…”
Section: Dust Dynamics In the Interplanetary Mediummentioning
confidence: 99%
“…The Al films are supported by the interchannel walls of a microchannel plate (MCP) detector and are freestanding over the open areas of the microchannels. Electrons Filmed MCPs exposed outside of the International Space Station (ISS) have been demonstrated as highly sensitive passive detectors of nanometer scale dust particles [9,10]. AFIDD consists of four circular, MCP detectors bearing Al films with two thicknesses, 2 × 10 and 2 × 100 nm.…”
Section: The Aluminium Film Interplanetary Dust Detector (Afidd)mentioning
confidence: 99%